Enhancing Algorithm Literacy and Digital Content through Technical Guidance on Coding and Artificial Intelligence for Junior High School Teachers in Karawang Regency - Uus Rusmawan; Henri Septanto; Tri Nur Arifin (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2026)
The rapid development of digital technology and Artificial Intelligence (AI) requires teachers to possess algorithm literacy competencies and the ability to utilize digital technology in learning processes. However, many junior high school teachers in Karawang Regency still face limitations in understanding coding concepts and the pedagogical use of AI. This Community Service Program (PkM) aims to enhance algorithm literacy and digital content creation skills of junior high school teachers through project-based technical guidance. The method employed was a participatory workshop using a Project-Based Learning approach, complemented by online mentoring. The participants consisted of 25 junior high school teachers in collaboration with LPK Maxy Academy. The results showed an average increase of 75% in teachers’ understanding of algorithm literacy and AI utilization based on pre-test and post-test comparisons. In addition, teachers successfully produced digital modules, interactive quizzes, and AI-based learning media. This program contributed to improved teacher work efficiency and encouraged more interactive and contextual learning. The findings indicate that technical guidance on coding and AI is effective in improving teachers’ digital competencies.